Surface Acting, Emotional Exhaustion, and Employee Sabotage to Customers: Moderating Roles of Quality of Social Exchanges - Zhang, Hui; Zhou, Zhiqing E.; Zhan, Yan; Liu, Chengbin; Zhang, Li (Frontiers in Psychology, 2018)
Abstract Using the conservation of resources theory and social exchange theory as our conceptual frameworks, the current study examined how employee surface acting relates to their sabotage to customers through the mediating role of emotional exhaustion, and explored the moderating roles of coworker exchange (CWX) and leader-member exchange (LMX). We collected two-wave time-lagged data from 540 clinical nurses and found that emotional exhaustion mediated the positive relationship between surface acting and employee sabotage to customers. In addition, we found that CWX buffered the positive effect of surface acting on emotional exhaustion, while LMX buffered the positive effect of emotional exhaustion on employee sabotage to customers, such that the effects were weaker when CWX and LMX were higher, respectively. These findings shed light on the effect of surface acting on employee harmful behaviors, the potential underlying mechanism, and boundary conditions to mitigate the negative consequences of surface acting.